A FUZZY-BASED BUSINESS DECISION MAKING SYSTEM: FROM A MULTI-OBJECTIVE PERSPECTIVE - Akinrotimi, Akinyemi Omololu; Abolore, Mabayoje Modinat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
In order to provide essential managerial services for making critical business-biased decisions, there is need for accurate data. A business activity hinged on an effective administrative course of action will not only portray the manager of the business as adept but also help advance the financial interests of the organization, while minimizing its losses in this respect. In this paper, a decision making model for controlling business activities is developed, using a fusion of linear programming methods and a set of fuzzy membership functions. In the research conducted, it is revealed that: to improve the effectiveness of a model used for making multiple objective decisions for business related activities, the use of a fuzzy method is more effective than the use of a non-fuzzy method in minimizing the objective functions. It was also discovered that when computing the objective functions of a problem, a more precise result can be obtained by fortifying a linear programming model, with a technique for managing imprecise data.